Too small to matter? Physicochemical transformation and toxicity of engineered nTiO₂, nSiO₂, nZnO, carbon nanotubes, and nAg - Ahamed, Ashiq (2022)
Engineered nanomaterials (ENMs) refer to a relatively novel class of materials that are increasingly prevalent in various consumer products and industrial applications - most notably for their superlative physicochemical properties when compared with conventional materials. However, consumer products inevitably degrade over the course of their lifetime, releasing ENMs into the environment. These ENMs undergo physicochemical transformations and subsequently accumulate in the environment, possibly leading to various toxic effects. As a result, a significant number of studies have focused on identifying the possible transformations and environmental risks of ENMs, with the objective of ensuring a safe and responsible application of ENMs in consumer products. This review aims to consolidate the results from previous studies related to each stage of the pathway of ENMs from being embodied in a product to disintegration/transformation in the environment. The scope of this work was defined to include the five most prevalent ENMs based on recent projected production market data, namely: nTiO2, nSiO2, nZnO, carbon nanotubes, and nAg. The review focuses on: (i) models developed to estimate environmental concentrations of ENMs; (ii) the possible physicochemical transformations; (iii) cytotoxicity and genotoxicity effects specific to each ENM selected; and (iv) a discussion to identify potential gaps in the studies conducted and recommend areas where further investigation is warranted.